2017
DOI: 10.1111/sjop.12383
|View full text |Cite
|
Sign up to set email alerts
|

The psychometric properties of the Portuguese version of the Personality Inventory for DSM‐5

Abstract: The DSM-5 Section III proposes a hybrid dimensional-categorical model of conceptualizing personality and its disorders that includes assessment of impairments in personality functioning (criterion A) and maladaptive personality traits (criterion B). The Personality Inventory for the DSM-5 is a new dimensional tool, composed of 220 items organized into 25 facets that delineate five higher order domains of clinically relevant personality differences, and was developed to operationalize the DSM-5 model of patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 27 publications
(59 reference statements)
3
18
0
1
Order By: Relevance
“…Third, considerable evidence has accumulated in favor of the hypothesis that the PID-5 trait domains can be conceived of as maladaptive variants of general personality traits [77,84,144,149,152,165,168,[173][174][175][176][177][178][179][180][181][182]. Specifically, negative affectivity was consistently associated with low emotional stability, detachment with low extraversion, antagonism with low agreeableness, and disinhibition with low conscientiousness.…”
Section: Convergent Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Third, considerable evidence has accumulated in favor of the hypothesis that the PID-5 trait domains can be conceived of as maladaptive variants of general personality traits [77,84,144,149,152,165,168,[173][174][175][176][177][178][179][180][181][182]. Specifically, negative affectivity was consistently associated with low emotional stability, detachment with low extraversion, antagonism with low agreeableness, and disinhibition with low conscientiousness.…”
Section: Convergent Validitymentioning
confidence: 99%
“…Finally, maladaptive traits have been found to be associated with a range of other variables, including age [75]; gender [75,217]; general symptom distress [66,77,84,172,[218][219][220]; psychotic disorder [221,222]; dissociative experiences [223]; bipolar disorder [224]; attention-deficit/hyperactivity disorder [225]; problematic alcohol use [66, 226•]; substance use [140,227,228]; self-harm [229]; pathological gambling [230]; internet-gaming disorder [231]; problematic internet use [223]; posttraumatic stress disorder [232, 233•]; physical illness [233•]; disability [57, [234][235][236]; quality of life [149,236]; self-esteem [150]; alexithymia [150]; empathy, self-reflection, and insight [150]; maladaptive schemas [237]; interpersonal problems [150,238,239]; pathological beliefs [240]; defensive styles [241]; emotion dysregulation [150,242]; anxiety mindset [205]; impulsivity [227]; aggression…”
Section: Convergent Validitymentioning
confidence: 99%
“…The PID-5 psychometric properties have been extensively examined and review studies have consistently shown it to be a reliable measure with internal consistency coefficients ranging from acceptable at the trait facets level to high at the domain trait level [ 7 ], and with the ability to capture individual differences that were stable during four weeks up to four months intervals [ 8 , 9 ]. Furthermore, in regards to its factor structure, the PID-5 confirmed a five-factor structure similar to the Five Factor Model (FFM), both in clinical and non-clinical studies and across different countries [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PID-5 has been translated into different languages and cultures and can be found in Arabic [ 23 ], Czech [ 24 ], Danish [ 25 ], Dutch [ 26 ], French [ 27 ], German [ 28 ], Indonesian [ 29 ], Italian [ 30 ], Norwegian [ 31 ], Persian [ 32 ], Polish [ 33 ], Portuguese [ 8 ], Brazilian-Portuguese [ 34 ], Russian [ 35 ], Spanish [ 36 ], and Swedish [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bach und Presnall-Shvorin 2020). Die postulierten DSM-5 und ICD-11 Trait-Domänen scheinen jedenfalls immer wieder empirisch erhärtet werden zu können und wurden auch in verschiedenen Kulturen repliziert (Bach et al 2017;Lotfi et al 2018;Pires et al 2017). Es gibt aber auch viele kritische Stimmen wie Paris (2020), der zwar grundsätzlich die Entwicklung begrüßt, jedoch Jahrzehnte von Forschung in Gefahr oder sogar verloren sieht.…”
Section: üBersichtsarbeit Paradigmenwechsel In Der Icd-11: Dimensionaunclassified